Bilateral pneumothorax after orthognatic surgery - Dario Bertossi; Luciano Malchiodi; Matteo Turra; Vincenzo Bondi; Massimo Albanese; Alessandra Lucchese; Francesco Carinci; Pierfrancesco Nocini (Wolters Kluwer Medknow Publications, 2012)
Among complications in orthognathic surgery, the insurgence of pneumothorax is very rare. Pneumothorax is the presence of air or gas in the pleural cavity and it is rare complications in the postoperative oral and maxillofacial surgery patient. The clinical results are dependent on the degree of collapse of the lung on the affected side. Pneumothorax can impair oxygenation and/or ventilation. If the pneumothorax is significant, it can cause a shift of the mediastinum and compromise haemodynamic stability. While 10% of pneumothoraces are asymptomatic, patients often complain of acute chest pain and difficulty breathing. There is a reduction in vital capacity, tachycardia, tachypnoea and a decrease in partial pressure of oxygen with an inability to maintain oxygen saturations. We observed this unusual surgical consequence in a 28-year-old female with negative clinical history and instrumental evaluation after Le Fort I osteotomy and bilateral sagittal split osteotomy (BSSO). No further consequences, no neurological sequelae, no infections and no other osteotomies sequelae were seen. Sudden post-surgical dispnea associated to sub-cutaneous emphysema of the neck and of the thorax must be adequately observed with the aim of monitoring further severe sequelae. The anaesthetic management of the emergency difficult airway in any post-surgical orthognatic treatment can be extremely difficult requiring a multi-disciplinary approach.